Fenestrated Endovascular Grafts for the Repair of Juxtarenal Aortic Aneurysms: An Evidence-Based Analysis (Medical Advisory Secretariat, 2009)
Endovascular repair of abdominal aortic aneurysm (AAA) allows the exclusion of the dilated aneurismal segment of the aorta from the systematic circulation. The procedure requires, however, that the endograft extends to the healthy parts of the aorta above and below the aneurysm, yet the neck of a juxtarenal aortic aneurysm (JRA) is too short for a standard endovascular repair. Fenestrated endovascular aortic repair (f—EVAR) provides a solution to overcome this problem by enabling the continuation of blood flow to the renal and visceral arteries through holes or ‘fenestrations’ in the graft. These fenestrations are designed to match the ostial diameter of the renal and visceral arteries. There are three varieties fenestration, small, large, and scallop, and their location needs to be customized to fit the anatomy of the patient. If the device is not properly designed, if the alignment is inaccurate, or if the catheterization of the visceral arteries is not possible, the procedure may fail. In such cases, conversion to open surgery may become the only option as fenestrated endografts are not retrievable. It is recommended that a stent be placed within each small fenestration to the target artery to prevent shuttering of the artery or occlusion. Many authors have noted an increased risk of vessel occlusion in unstented fenestrations and scallops. Once placed in a patient, life-long follow-up at regular intervals is necessary to ensure the graft remains in its intended location, and that the components have adequate overlap. Should the need arise, routine follow-up allows the performance of timely and appropriate intervention through detection of events that could impact the long-term outcomes. ALTERNATIVE TECHNOLOGY: The technique of fenestrated endovascular grafting is still in evolution and few studies have been with published mid-term outcome data. As the technique become more common in vascular surgery practices, it will be important to determine if it can provide better outcomes than open surgical repair (OSR). In an OSR approach, aortic clamping above one or both renal arteries, or above the visceral arteries, is required. The higher the level of aortic clamping, the greater the risk of cardiac stress and renal or visceral ischemia. During suprarenal or supraceliac aortic clamping, strain-induced myocardial ischemia may also occur due to concomitant rise in cardiac afterload and a decrease in cardiac output. Reports indicate that 6% of patients undergoing surgical repair develop myocardial infarction. The ideal level of clamp location remains controversial with conflicting views having been reported. METHOD: A search of electronic databases (OVID MEDLINE, MEDLINE In-Process & Other Non-Indexed Citations, EMBASE, The Cochrane Library, and the International Agency for Health Technology Assessment [INAHTA] database was undertaken to identify evidence published from January 1, 2004 to December 19, 2008. The search was limited to English-language articles and human studies. The automatic search alerts were received and reviewed up to March 23, 2009. The literature search and automatic search update identified 320 citations, of which 13 met inclusion/exclusion criteria. One comparative study presented at an international seminar, five single-arm studies on f—EVAR, and 7 studies on OSR (one prospective and six retrospective) were considered for this analysis. To grade the strength of the body of evidence, the grading system formulated by the GRADE working group and adopted by MAS, was applied. The GRADE system classifies evidence quality as high (Grade A), moderate (Grade B), or low (Grade C) according to four key elements: study design, study quality, consistency across studies, and directness. A summary of the characteristics of the f—EVAR and OSR studies found through the literature search is shown in Table ES-1. MORTALITY OUTCOMES: The pooled estimate for 30-day mortality was 1.8% among the f—EVAR studies and 3.1% among the OSR studies that reported data for the repair of JRA separately. The pooled estimate for late mortality was 12.8% among the f—EVAR studies and 23.7% among the OSR studies that reported data for JRA separately. VISCERAL ARTERY EVENTS REPORTED IN F—EVAR STUDIES: RENAL EVENTS DURING F-EVAR: A total of three main renal arteries and two accessory renal arteries became occluded during the procedure. These were all due to technical issues, except one accessory renal artery in which the artery was intentionally covered. One patient required open surgery following the procedure. RENAL EVENTS DURING THE FOLLOW-UP: A total of 12 renal arteries (12 patients) were found to be occluded during follow-up. In two patients, the same side accessory renal artery was also occluded. Four (1.5%) patients lost one kidney and five (2.3%) patients underwent dialysis, three (1.4%) of which became permanent. A total of 16 cases of renal artery stenosis (16 patients) occurred during follow-up. Eight of these were treated and eight were observed. Segmental renal infarcts were found in six patients but renal function was not impaired. MESENTERIC EVENTS DURING F-EVAR: Three mesenteric events occurred during the f—EVAR procedures resulting in two deaths. One patient developed bowel ischemia due to embolization of the superior mesenteric artery (SMA); this patient died 13 days after the procedure from multiorgan failure. One patient died eights days after the procedure from mesenteric ischemia and bowel perforation. The third SMA event occurred during surgery with subsequent occlusion in early follow-up. MESENTERIC EVENTS DURING FOLLOW-UP: During follow-up, five (1.8%) SMA occlusions/partial occlusions and one SMA stenosis were noted. Three of the five patients with SMA occlusion/partial occlusion remained asymptomatic and no further intervention was necessary. One patient underwent SMA bypass surgery and in two patients, the problem solved by SMA stenting. A summary of the outcomes reported in the f—EVAR and OSR studies is shown in Table ES-2. SUMMARY: Short- and medium-term results (up to 2 years) of f—EVAR for the repair of JRA showed that outcomes in f—EVAR series compare favourably with the figures for the OSR series; however, uncertainty remains regarding the long-term results. The following observations are based on low quality evidence. F—EVAR has lower 30-day mortality than OSR (1.8% vs. 3.1%) and a lower late-mortality over the period of time that patients have been followed (12.8% vs. 23.7%). There is a potential for the loss of target vessels during or after f—EVAR procedures. Loss of a target vessel may lead to loss of its respective end organ. The risk associated with this technique is mainly due to branch vessel ischemia or occlusion (primarily among the renal arteries and SMA). Ischemia or occlusion of these arteries can occur during surgery due to technical failure and/or embolization or it may occur during follow-up due to graft complications such as graft migration, component separation, or arterial thrombosis. The risk of kidney loss in this series of f—EVAR studies was 1.5% and the risk of mesenteric ischemia was 3.3%. In the OSR studies, the risk of developing renal insufficiency was 14.4% and the risk of mesenteric ischemia was 2.9%. F—EVAR has a lower rate of postoperative cardiac and pulmonary complications. Endoleak occurs in 22.5% of patients undergoing f—EVAR (all types) and about 8% of these require treatment. Most of the interventions performed to treat such endoleaks conducted using a minimally invasive approach. Due to the complexity of the technique, patients must be appropriately selected for f—EVAR, the procedure performed by highly experienced operators, and in centers with advanced, high-resolution imaging systems to minimize the risk of complications. Graft fenestrations have to be custom designed for each patient to fit and match the anatomy of their visceral arteries. Planning and sizing thus requires scrutiny of the target vessels with a high degree precision. This is important not only to prevent end organ ischemia and infarction, but to avoid prolonging procedures and subsequent adverse outcomes. Assuming the average cost range of FEVAR procedure is $24,395-$30,070 as per hospital data and assuming the maximum number of annual cases in Ontario is 116, the average estimated cost impact range to the province for FEVAR procedures is $2.83M-$3.49M annually.